MUSIC EDUCATION IN POLAND ON THE THRESHOLD OF THE THIRD MILLENNIUM - Dymon, Mirosław (Aura musica, 2021)
The article deals with the most important changes in the music education system in Poland, which are still being continued. Like everything new, it must encounter various formal and substantive obstacles, as well as the emergence of many extreme emotions in shaping the new face of Polish musical reality in the areas of broadly understood culture. In order to better understand the process of changes and dynamization of individual sectors, the article will outline the assumptions of the education reform from 1999 to the last from 2017. The structure of music education over this period has undergone many transformations, supplements and even changes in the basic overall assumptions regarding the education system in Poland. However, there are still postulates that seem to wait for further studies and solutions, both in the general music and art education, constituting a separate section with its own structure.
Keywords: education; music; art schools; reforms